Downwind of the Atomic State: US Continental Atmospheric Testing, Radioactive Fallout, and Organizational Deviance, 1951–1962. Issue 4 (1st December 2015) - Rice, James
Abstract : The Atomic Energy Commission (AEC) conducted more than 100 atmospheric atomic detonations at the Nevada Test Site (NTS) between 1951 and 1962 depositing radioactivity throughout the United States but particularly the rural communities just "downwind." The monitoring of radioactivity and efforts to warn downwind residents, however, failed to ensure their safety. I engage in archival analysis of AEC documents to examine decision making in reference to radioactive fallout. In recounting the socionatural history of atmospheric testing at the NTS, the present study argues operational conduct was lethargic due to the adoption of specious organizational heuristics. They included the assumption that fallout is subject to predictable atmospheric dispersion; fallout has noncumulative, undifferentiated effects on people; and downwind residents were prone to unreasoning panic. Thus AEC officials were continually chasing problems after they arose and in the absence of containment of fallout focused on containment of public perception and dialogue. The study concludes by highlighting the lessons relevant to contemporary sociotechnical activities.